Simulation Study of Messenger Molecule Displacement in Communication via Diffusion - Kaur, AP; Randhawa, DKK; Walia, GK (International Journal of Computer Sciences and Engineering, 2025)
Molecular Communication via diffusion (MCvD) is a new communication paradigm that uses molecules as the information carrier between the nano-machines. The end to end MolecUlar CommunicatIoN (MUCIN) simulator tool is used to explore the characteristics of the MCvD channel. This simulator considered Binary Concentration Shift Keying (BCSK) technique for modulating binary information symbols, support 1-dimensional environment, and send symbols consecutively. The main issues of MCvD system are the Inter-Symbol Interference that arises when the molecules belonging to the previous symbol come into the current symbol. Conventional MCvD system exhibits a long tail of received molecular histogram, results in higher ISI. In this paper, the displacement of a messenger molecule is increased to reduce the amount of stray molecules in the MCvD channel. The proposed technique shows the first hitting time distribution to determine the highest reception of the information carrying molecules by the receiver. We also evaluate the performance of proposed scheme for different values of step length in terms of Inter- Symbol Interference (ISI), symbol detection and communication delay. Our results indicate that introducing proposed technique significantly improves the performance of MCvD system.